Teaching Materials for Algebra and Linear Programs Based on Pancasila Student Profiles - Kesumawati, Nila; Fuadiah, Nyiayu Fahriza; Lusiana, Lusiana; Octaria, Dina (Jurnal Riset Pendidikan Matematika, 2023)
The aims of this study were: 1) to develop textbooks based on Pancasila student profiles for Algebra and Linear Programming courses; and 2) developing instruments to measure the achievement of the dimensions of the Pancasila student profile. The quality of the products developed is assessed based on: 1) validity aspects, 2) practical aspects, and 3) effectiveness aspects of students' mathematical creative and critical thinking abilities. The research method used is the ADDIE Research and Development (R & D) model. The research subjects were 19 students in the first semester of the Mathematics Education Study Program. The instruments used to obtain the quality of the textbooks developed were: 1) textbook assessment sheets to measure validity, 2) response questionnaires and observation sheets to measure practicality, 3) critical thinking skills and mathematical creative questions to measure effectiveness. The validity quality of textbooks fulfilling the valid criteria is shown by the average score of 3.53 out of a maximum score of 4 which means that it is very valid for practicality quality to get an average score of 3.32 out of a maximum score of 4 which means practical, quality of effectiveness in terms of critical thinking skills and creative mathematical students who meet the affective criteria are shown, namely 58% which means sufficient and the average score for critical and creative thinking skills is 67.27 which means quite effective. Textbooks and RPS are suitable for use in lectures